High-frequency repetitive transcranial magnetic stimulation protects against 6-OHDA-induced Parkinson’s disease symptoms by modulating the proNGF-p75NTR-sortilin pathway - Rui Zhao; Wanqing Du; Ke Tian; Kunlong Zhang; Hua Yuan; Fang Gao; Xin Kang; Xiaolong Sun (PeerJ, 2025)
Background High-frequency repetitive transcranial magnetic stimulation (HF rTMS) is a promising non-invasive treatment for Parkinson’s disease (PD) in clinical settings. However, the precise mechanisms are incompletely understood. The proNGF-p75NTR-sortilin signaling pathway is closely associated with nigrostriatal dopaminergic (DA) neuron degeneration, a hallmark feature of PD. This study aimed to evaluate the neuroprotective efficacy of HF rTMS on the proNGF-p75NTR-sortilin pathway in PD. Methods Using a PD rat model induced by 6-hydroxydopamine (6-OHDA), the rats were randomly divided into two groups: sham rTMS group and HF rTMS group. After a 4 w intervention, the rats’ motor function was assessed using a rotarod test. Additionally, immunofluorescence technology was used to analyze the DA neurons in the midbrain of PD rats, and immunohistochemistry and Western blot analysis were employed to evaluate the expression levels and effects of proNGF-p75NTR-sortilin in the midbrain following HF rTMS. Results Our research revealed a significant increase of proNGF expression in reactive astrocytes and upregulated sortilin and p75NTR in DA neurons in the substantia nigra of the hemisphere ipsilateral to the induced lesion, correlated with the degeneration of DA neurons and impaired motor functions. A four-week regimen of HF rTMS, as opposed to sham rTMS, significantly improved the above pathological conditions. The decrease in proNGF-p75NTR-sortilin expression following HF rTMS correlated with a significant increase in DA neuron survival and motor function improvement. HF rTMS exhibited no effects on proBDNF expression. Our study findings indicate that the targeted proNGF-p75NTR-sortilin complex modulation may be an essential mechanism through which HF rTMS exerts its neuroprotective effect. This insight offers a new therapeutic perspective for PD management, highlighting the potential of rTMS to modulate key neurodegenerative pathways.